2014
DOI: 10.12738/estp.2014.2.1493
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Democracy of Primary School Students

Abstract: The aim of this study is to identify the perceptions of democracy of primary school students, identify the factors that affect these, and compare the results with those obtained from other countries. The research was carried out during the 2011-2012 school year with 1,667 students from the 6th, 7th, and 8th grades who were chosen from 26 cities in Turkey using the stratified sampling model. The Democracy Perception Scale was used as a data collection tool. According to the findings of the study, the democratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 9 publications
3
11
0
Order By: Relevance
“…In another research, democracy perceptions of primary school students are researched and significant differences are found regarding the concepts of equality, human rights, independence. The research supports the related study in terms of these results [12]. As a result, at the end of process which attempts to reveal perceptions of participants on democracy through metaphors, it seems that teacher candidates have developed a number of validated metaphors related to the topic.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…In another research, democracy perceptions of primary school students are researched and significant differences are found regarding the concepts of equality, human rights, independence. The research supports the related study in terms of these results [12]. As a result, at the end of process which attempts to reveal perceptions of participants on democracy through metaphors, it seems that teacher candidates have developed a number of validated metaphors related to the topic.…”
Section: Resultssupporting
confidence: 82%
“…According to results of obtained findings in research process, it is seen that social science teacher candidates have developed 28 valid metaphors related to democracy. When look at developed metaphors, it is understood that mostly freedom (19), scale (12), water (8) simulations are repeated; at least gift, utopia, dream, child, medicine, oxygen and sky (1) simulations are repeated. At the results of that developed metaphors (simulations) by candidate candidates regarding concept of democracy accumulate under certain themes; "vital-social aspect (49)", "management aspect (49)", "science-education aspect (7)" results have been obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaldırım (2005) concludes that 87% of the pupils were aware of the importance of equality between men and women for democracy and that 61% believed that amending the laws in favour of women would be a democratic action. In Kuş and Çetin (2014), a survey study with secondary school pupils, the girls were found to be more sensitive than the boys about equality between men and women, and to have significantly different scores in democratic value perceptions.…”
Section: Discussionmentioning
confidence: 96%